Media Development Pop Up Book Kota Onde-Onde To Stimulate Early Literacy Skills Of Children Aged 5-6 - Susanti, Elly (Proceedings Series of Educational Studies, 2024)
Based on the observations of researchers, the cause of the lack of maximum ability of students in early literacy is because teachers are still less interesting in providing activities in learning, so that students are easily bored and not interesting for students. This study aims to develop Pop Up Book Media onde-onde City, evaluate the impact of the stimulation of early literacy skills and is expected to provide positive learning and a solid foundation for further development and test the feasibility and effectiveness. The type of research used is Research Development (Research & Development) or commonly abbreviated as R&D. The development research Model that will be used by researchers in developing media Pop Up Book onde-onde City is ADDIE model. The results of this study were seen based on the implementation of product trials conducted in TK Dharma Wanita Mojokerto with a small group test of 5 students obtained a final percentage value of 74% (Valid) and in TK Taman Indria 01 Malang obtained a final percentage value of 88% (very Valid), while for large group trials in TK Dharma Wanita Mojokerto totaling 11 students obtained a final percentage value of 92%(very Valid) and in TK Taman Indria 01 Malang obtained a final percentage value of 94% (very Valid). Thus, the Pop Up Book media of Onde-onde City is declared worthy to be used in the learning process of children aged 5-6 years. Keywords: Media; Pop Up Book; Early Literacy